Spatial Analysis of Rainfall, Humidity, Temperature Factors on Dengue Hemoraghic Fever Case in East Java 2019 - Sinta Rizki Agustin; Alysha Lalita Aryanti; Feby An'nisa Putri Harahap; Virli Andani Harnelis; Grace Hana Rapar; Lulu Fajria Qotrunnada; Nada Syifa; Nurul Fathiya Rizqina; Shabrina Banafsaj Zata Amani; Farhan Adrian; Al Asyary; Ema Hermawati (UHAMKA Press, 2020)
Background: Dengue hemorrhagic fever (DHF) is a disease with high morbidity and mortality in Indonesia caused by Aedes aegypti and Aedes albopictus bites that carry the dengue virus. Environmental factors such as rainfall, temperature, and humidity are among the factors that affect the incidence rate of the disease. East Java is one of the provinces in Indonesia with high dengue cases in 2019, namely 18,397 cases.Methods: The analysis carried out in this study is an observational analysis using multi-temporal analysis and statistical regression tests using data on the incidence of DHF and climatological data in the form of temperature, humidity, and rainfall. The study uses 2 analyses, which is spatial analysis and bivariate analysis. Before performing data analysis, the data is tested for normality using the normality test. A spatial analysis is then made with QGIS to visualize the data into a map so that the relationship between the DBD case and the climatological factor can be seen more clearly.Results: The results of statistical tests using the ANOVA test showed significant results with p = 0.022 and an R-square of 0.138. Meanwhile, for the Pearson correlation test, there is a moderate positive relationship between rainfall and cases. Based on the ANOVA tests performed on the case data and temperature, it is known that there is no correlation between the case and temperature due to the p value of 0.94, which is greater than 0.05, however, the Pearson correlation test results in an R-squared value of 0.031, which indicates a correlation between the temperature and dengue cases by 3.1 %. Based on the ANOVA test and the Pearson correlation test performed on cases and humidity, it is known that there is no correlation between the dengue cases and the humidity.Conclusion: In previous studies, it was known that climatic factors such as rainfall, temperature, and humidity could affect the incidence of Dengue Fever due to the activity of mosquito vectors. Based on the statistical test analysis through SPSS conducted by the researchers this time, only temperature and humidity had a relationship with the incidence of DHF. A preventative measure can be done by monitoring climate patterns so that dengue cases can be controlled on time to control dengue cases in East Java.